Meta-Analysis: The Effect of Problem-Based Learning Assisted GeoGebra Software on Students Mathematic Ability - Vera Anzani; Dadang Juandi (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
Problem Based Learning (PBL) is a learning model that is often used in learning mathematics. This meta-analysis study was conducted to summarize the effect of PBL with the help of GeoGebra software on students' mathematical abilities. Related databases were searched for studies that met the inclusion criteria. The estimation method uses a random-effect model with a 95% confidence interval. This study analyzed 5 primary studies published between 2016 and 2020 using the posttest-only group design experimental research method, and 320 students were involved. The Comprehensive Meta-Analysis (CMA) program was used to assist the analysis. As a result of the study, the overall effect size was 1.32 (strong effect) with a standard deviation of 0.021. Analysis of study characteristics revealed that the influence of the PBL model assisted by GeoGebra applications had a strong effect on the condition of the sample size of 1-40 students, secondary school education level and on mathematical problem-solving abilities. This finding is considered by practitioners of mathematics education to implement it in mathematics learning.